Fragmentation studies by non-explosive cylinder expansion technique - Rao, Prakash; Painter, Jonathan; Appleby-Thomas, Gareth J.; Critchley, Richard; Wood, David C.; Roberts, Andrew; Hazael, Rachael (Elsevier, 2020)
Expansion and fragmentation of metallic cylinders is an important area of study both for designing munitions and mitigation techniques against fragments as well as in the failure of pressurised pipes in industry. Most of the reported studies on fragmentation have been carried out by detonating explosively filled metallic cylinders. However, this approach has inherent limitations in terms of both safety and repeatability – not least due to packing issues with explosive fills. Fragmentation studies on hollow metallic cylinders of both mild and stainless steel of various thicknesses (2–4 mm) were carried out by firing a polycarbonate projectile from a single-stage light gas gun. Strain rates of the order of 2 × 104 s−1 were observed at cylinder expansion velocities of 400–450 m s−1, calculated from flash X-ray radiographs. The differences in fragmentation behaviour of both materials was observed, attributed to their different response to high strain-rate loadings. Microscopic analysis of mild steel fragments showed interesting alignment of ferrite and pearlite grains, similar to reported effects of explosive loading. This suggests the potential to employ this technique to simulate explosive cylinder expansion in a non-explosive laboratory environment enabling a convenient recovery of fragments. Numerical modelling with using ANSYS AUTODYN® allowed for a better understanding of the various parameters controlling expansion and fragmentation. Analysis of recovered fragments by a Fragment Weight Distribution Map (FWDM), a method generally used for characterising pipe bombs, could clearly demonstrate the effect of casing material and thickness.
Keywords: Gas-gun; High strain rate; Mild steel; Stainless steel; Microstructure